Development and Optimization of Fixed Dose Antihypertensive Combination Drugs using Double Layer Sustained Release Microsphere Technology - Dan, Shubhasis; K. Malik, Jitender; Singh, Navjot; Bharati, Dileep; Bose, A. (Asian Journal of Chemistry, 2011)
For the development of double walled microspheres, two polymers i.e., chitosan and eudragit E100 were selected . The inner core which is made up of polymer chitosan will contain drug; propranolol hydrochloride and outer shell which is made up of polymer eudragit E100 contain; frusemide. Since eudragit E100 is dissolving below pH 5, will release the drug (furosemide) and attain therapeutic plasma concentration, which reduces the body fluid thus reduces blood pressure then the inner core chitosan's is a mucoadhesive, contains propranolol hydrochloride, adhesive to mucous layer of stomach or GIT will provide the sustain release of the drug for a longer period (24 h). Therefore, it is the goal of present study to adapt methods of doublewalled fabrication with modifications, for the successful encapsulation of water-soluble. Propanolol hydrochloride and water insoluble furosemide, resulting in reduced-initial bursts as well as sustained release profiles suitable for the treatment of hypertension.